Up-scalable synthesis of size-controlled NiSe nanoparticles using single step technique - Al-Hada N.M.; Kasmani R.M.; Kasim H.; Al-Ghaili A.M.; Saleh M.A.; Baqiah H.; Al-Asbahi B.A.; Yang J.; Noorazlan A.M.; Li Q.; Liu J.; Ahmed A.A.A.; et al. (Elsevier Editora Ltda, 2023)
Electron spin resonance spectroscopy; Energy dispersive X ray analysis; Energy gap; Fourier transform infrared spectroscopy; Heat treatment; High resolution transmission electron microscopy; Magnetic moments; Metal nanoparticles; Nanomagnetics; Particle size analysis; Synthesis (chemical); Thermoanalysis; X ray diffraction analysis; Calcination temperature; Energy bandgaps; Magnetic characteristic; Nise nanoparticle; Optical characteristics; Particle dimensions; Scalable synthesis; Structural characteristics; Thermal treatment technique; Treatment techniques; Nickel compounds